Biodegradation of PCL and PVC: Chaetomium globosum (ATCC 16021) activity - Vivi, Viviane Karolina [UNESP]; Martins-Franchetti, Sandra Mara [UNESP]; Attili-Angelis, Derlene [UNESP] (Springer Nature, 2018)
The increasing use of plastics in human activities has resulted in an enormous amount of residues which became a matter of great environmental concern. Scientific studies on the microbial degradation of natural and synthetic molecules show the potential of fungal application on cleaning technologies. The biodegradation of PCL (polycaprolactone) and PVC (polyvinyl chloride) films by Aspergillus brasiliensis (ATCC 9642), Penicillium funiculosum (ATCC 11797), Chaetomium globosum (ATCC 16021), Trichoderma virens (ATCC 9645), and Paecilomyces variotii (ATCC 16023) was studied. According to ISO 846-1978—“Testing of Plastics - Influence of fungi and bacteria”, samples of the studied polymers were inoculated with a mix suspension of 106 fungal inoculum and maintained in moisture glass chambers in a bacteriological incubator at 28 °C for 28 days. The samples were analyzed by means of morphological and color changes, mass loss, optical microscopy (OM), and scanning electron microscopy (SEM) after 28 days of culturing. After the incubation period, visual observations of the PCL films showed many micropores and cracks, pigmentation, surface erosion and hyphal adhesion on the sample surfaces, and a mass loss of up to 75%. On the contrary, there was no evidence of PVC biodegradation, such as changes in color and significant mass loss. Chaetomium globosum ATCC 16021 was a pioneer in the colonization and attack of PCL, resulting in significant mass losses. Although PVC was less attacked by the ascomycete, the polymer supported the adhesion and growth of its fertile structures (perithecia), suggesting the fungal potential to degrade both plastics.